Pengembangan Mesin Penanam dan Pemupuk Jagung Terintegrasi dengan Pengolahan Tanah Alur - Agustami Sitorus; Wawan Hermawan; Radite Praeko Agus Setiawan (Jurnal Keteknikan Pertanian, 2015)
The prototype of integrated corn planter and fertilizer applicator for strip tillage has been developed. The development was done by using wheel axis of hand tractor for driven rotor fertilizer applicator and metering device corn planter. Planting furrows were made into two furrows on a single pass with strip tillage. The objective of this study was to develop and to conduct performance test of the corn planting and fertilizing for strip tillage. Stationer test result showed that the fertilizer applicator and corn planter performance could be metering 20.71 g/m NPK fertilizer and 1-3 seeds of corn per planting hole respectively. Field test result showed that the fertilizer applicator and corn planter performance could be metering 15.88 g/m NPK fertilizer and 1-2 seeds of corn per planting hole respectively. Mean seed spacing was 21.5 cm which was longer than the theoretical seed spacing (20 cm). Fertilizer and seed hopper capacity were 16.53 kg and 1kg respectively. Effective fieldcapacity was 0.147 ha/h (low-1)and 0.350 ha/h (low-2) and efficiency for respective speed was 76.24% and 83.78%.